Chapter 4 - Wheat - Mar, Talita Bernardon; Lau, Douglas; da Silva, Fabio Nascimento; Alemandri, Vanina Maria; Da Silva Pereira, Paulo Roberto Valle (Elsevier, 2024)
Wheat is a grass that has been cultivated for over 10,000 years since the beginning of agriculture in the Fertile Crescent and then spread to different regions of the world. Virus species, from distinct families, with different strategies of replication, dissemination, protein expression, and transmission by vector organisms cause significant damage to yield. This chapter provides a general view of the virus species reported infecting wheat worldwide.